People of the songtrail : a novel of North America's forgotten past - Gear, W. Michael; Gear, Kathleen O'Neal (Gear, Kathleen O'Neal. North America's forgotten past series., 2015)
People of the Songtrail is the saga of the first European settlers to land on the shores of the New World. It is a story, like so many in America's history, of the swift and violent clash of cultures, and of extraordinary men and women on both sides who were brave enough to work for the fragile hope of peace.